Normative values of the range of motion of movements at the wrist joint for hockey players: a cross-sectional study - Verma, N.; Esht, V.; Mehra, P.; Alshehri, M. M.; Kashoo, F. Z.; Khan, A. R.; Shaphe, M. A.; Khan, M.; Alghadir, A. H. (Medicina dello Sport, 2023)
BACKGROUND: Wrist range of motion (ROM) is used to objectively evaluate treatment outcomes for wrist interventions. Wrist kinetics and kinematics are critical for diagnosing and treating traumatic or degenerative abnormalities in the wrist joint. In field hockey, wrist motions are crucial for selecting excellent shots like hockey wrist shots, snap shots, slap shots, etc. This study aimed to find the normative values of active ROMs (AROMs) of wrist joints for the hockey and non-athletic populations.